Performance evaluation of uncoated and coated carbide tools when drilling titanium alloy - Abd. Rahim, Erween (2005)
Titanium alloys are widely used in the aerospace industry especially in airframes and engine components due to their high strength-weight ratio that is maintained at elevated temperature and their exceptional corrosion resistance. Nevertheless, titanium and its alloys are thought to be difficult-to-machine material due to their poor thermal properties and highly chemical reactivity. In this study, Ti- 6Al-4V has been drilled using single-layer PVD-HIS-TiAlN coated carbide, Type A (T12-A) and Type C (T12-C and T13-C), multi-layer PVD-HIS-Supernitride coated carbide, Type A (S13-A) and Type C (S12-C and S13-C) and uncoated carbide Type B (U12-B and U13-B) and Type C (U12-C and U13-C) drills with different drill point geometry under various cutting speeds and constant feed rate. The tool performance, tool failure modes and tool wear mechanisms were analyzed under various cutting speeds. On the other hand, the cutting forces and the surface roughness were measured. In this study, Type C drills outperformed Type A and B drills in terms of tool life for almost all the cutting conditions tested. At low cutting speed of 25 m/min, the uncoated carbide tool of U12-C drills demonstrated the longest tool life, which resulted in low tool wear rate. The excellent improvement of both coated drills were mainly due to their ability of maintaining oxidation resistance and high hardness especially at elevated temperatures. On the other hand, poor performance of Type B drills was mainly due to premature tool failure caused by severe chipping and breakage. Non-uniform flank wear, chipping, cracking and catastrophic failure were the dominant failure modes of all tools under most cutting conditions tested. These failure modes were mainly associated with adhesion, diffusion and plastic deformation wear mechanisms. Based from the results obtained, it can be suggested that Type C drill was recommended and the lower cutting speed of 25 m/min should be employed in order to achieve high performance in drilling Ti-64.